Born for trouble : the further adventures of Hap and Leonard : stories - Lansdale, Joe R., 1951- (Lansdale, Joe R., 1951- Hap and Leonard series., 2022)
In Edgar Award winner Joe R. Lansdale's newest Hap and Leonard story collection, the boys are back with more righteous ass-kickings, highly improbable adventures, and disastrous fishing trips. These never before collected tales showcase the popular not-so dynamic duo who are little bit older, but not a whole lot wiser--Hap and Leonard were truly born for trouble.